Pengaruh Latihan Fisik Terhadap Indeks Massa Tubuh Tenaga Rescuer Di Kantor Pencarian Dan Pertolongan Kelas B Palangka Raya - Shaleh, Muhammad; Carolina, Putria; Rosela, Kristin (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
An imbalanced body mass index increases the risk of various diseases and affects career paths, requiring rescuers to have a BMI with ideal weight and height. Physical exercise is expected to improve and help maintain BMI within the normal range. This is prepared for individuals, especially rescuers, in good physical, technical, tactical, and psychological (mental) condition and improves rescue workers who are always ready in any situation. The purpose of this study was to determine the effect of physical exercise on BMI in rescuers at the Class B Search and Rescue Office in Palangka Raya. This study used a one-group pre-test and post-test design. The sample of this study was the Rescuers of the Class B Search and Rescue Office in Palangka Raya. The number of samples with (Simple Random Sampling) was 42 samples. Data collection was conducted on June 10-24, 2025 for 2 weeks using an observation sheet. Pre-IMT and Post-IMT were given physical exercise interventions 5 times in 1 month. Data analysis used comparative analysis with statistical tests T-test, Paired T-test. Results of the 42 respondents, there were research results showing changes in BMI Pre-test were normal in 31 people (74%), pre-obese in 8 people (19%), obese in 3 people (7%), BMI Post-test with normal values in 32 people (76%), pre-obese in 9 people (22%) and obese in 1 person (2%). The results of the statistical test P value = 0.001 or a significance level of p < 0.05, so H1 is accepted that there is an effect of physical exercise on Body Mass Index marked by the pre-BMI value to post-BMI in Rescuer personnel. There is an influence of physical exercise on the Body Mass Index, indicated by the pre-BMI to post-BMI value in rescue workers, where there is a significant change after physical exercise